2012
DOI: 10.1088/1742-6596/369/1/012030
|View full text |Cite
|
Sign up to set email alerts
|

Radiative heat transfer modelling in a concentrated solar energy bubbling fluidized bed receiver using the Monte Carlo Method

Abstract: According to recent studies in the solar energy community, a promising ways of solar energy conversion seems to be the beam down concentration technology associated to a fluidized bed receiver. The advantage of this system is its ability to heat air at temperature reaching 1000 K in a receiver directly exposed to a concentrated solar beam and integrated in a thermodynamic cycle. This paper focus on the modelling of radiative heat transfer from the optical concentrator to the receiver by taking into account abs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
0
5
0
Order By: Relevance
“…In the case of SiC particles, previous results have shown that the dependency of the radiative properties on the wavelength is not significant in the solar spectrum (Baud et al, 2012). From the complex index of refraction of SiC particles found in the Handbook of optical constants of solids (1985), we can thus calculate averaged values of optical properties Q s , Q a and g. Subsequently, we performed grey calculations where the optical properties are described by the following values of the absorption and scattering cross sections:…”
Section: Radiative Properties Of the Particles In The Receivermentioning
confidence: 96%
“…In the case of SiC particles, previous results have shown that the dependency of the radiative properties on the wavelength is not significant in the solar spectrum (Baud et al, 2012). From the complex index of refraction of SiC particles found in the Handbook of optical constants of solids (1985), we can thus calculate averaged values of optical properties Q s , Q a and g. Subsequently, we performed grey calculations where the optical properties are described by the following values of the absorption and scattering cross sections:…”
Section: Radiative Properties Of the Particles In The Receivermentioning
confidence: 96%
“…FB solar receivers have been investigated as early as in the '80s, with layouts spanning from the proof-of-concept to the lab-scale levels: dense stationary gas FB, dilute-or dense-phase circulating FB (Flamant, 1982;Bachovchin et al, 1983;Megahed et al, 1988;Haddad and Elsayed, 1988;Koenigsdorff and Kienzle, 1991;Sasse and Ingel, 1993;Werther et al, 1994;Baud et al, 2012;Chirone et al, 2013;Flamant et al, 2013;Ma et al, 2014;Marti et al, 2015;Reyes-Belmonte et al, 2019;Farsi and Dincer, 2019;Díaz-Heras et al, 2020a). The extension of these concepts to the industrial scale is a matter still deserving thoughtful investigation.…”
Section: Present and Perspective Applications Of Fluidized Bed Solar Receivers And Reactors Solar Energy Collection With Thermal Energy Smentioning
confidence: 99%
“…To simulate optical systems, many softwares or development environments have been developed such as Mirval, Soltrace, Stral and Tonatiuh, [2], EDStar [17]. They commonly use the Monte Carlo ray-tracing to predict the concen- [3], [4], [9].…”
Section: Modeling Of Radiative Heat Transfermentioning
confidence: 99%
“…The raytracing is detail in the following procedure: 6. change the system of reference by rotation of angle −β 2 in order to be in the reference of the secondary;…”
Section: Advances Inmentioning
confidence: 99%